Peningkatan Kesadaran Masyarakat Tentang Infeksi Tuberkulosis Paru Pasca Covid-19 - Suriyani Tan; Rina K. Kusumaratna; Yuliana Yuliana; Machrumnizar Machrumnizar (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Pulmonary tuberculosis, often called TB, is a bacterial infection caused by Mycobacterium tuberculosis. Indonesia is one of eight countries that accounts for 2/3 of TB cases worldwide. This disease usually affects the lungs, but can also attack other organs in the body. TB symptoms can vary depending on the type of infection and the organs affected. During the COVID-19 pandemic, attention to other diseases, such as TB has decreased. The increasing risk of spreading TB after COVID-19 is a public health concern. Restrictions on social movement implemented during the COVID-19 pandemic may result in an increased risk of TB transmission among close contacts of TB sufferers. People who have had COVID-19, especially those who have had lung damage due to COVID-19 infection, may have a higher risk of developing TB due to a weakened immune system. This Community Service is carried out to increase public awareness of the dangers of TB that continue to lurk after COVID-19 and it is hoped that through this outreach and education, the public will become more aware of the symptoms of TB so they can check themselves at Primary Health Care.